2001
DOI: 10.1120/jacmp.v2i3.2605
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning of a mobile electron accelerator for intraoperative radiotherapy

Abstract: Radiation performance characteristics of a dedicated intraoperative accelerator were determined to prepare the unit for clinical use. The linear accelerator uses standing wave X‐band technology (wavelength approximately 3 centimeters) in order to minimize the mass of the accelerator. The injector design, smaller accelerator components, and low electron beam currents minimize radiation leakage. The unit may be used in a standard operating room without additional shielding. The mass of the accelerator gantry is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…The depth of d max , R 90 , and R 80 values are comparable to those published by Mills et al. for the Mobetron 1000, falling largely within 2 mm of the values reported there 15. The 12 MeV beam exhibits larger differences, up to 5 mm for R 80 .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The depth of d max , R 90 , and R 80 values are comparable to those published by Mills et al. for the Mobetron 1000, falling largely within 2 mm of the values reported there 15. The 12 MeV beam exhibits larger differences, up to 5 mm for R 80 .…”
Section: Resultssupporting
confidence: 79%
“…Experience commissioning a previous model of the Mobetron, the Mobetron 1000, has been reported previously 15. However, in the time since that publication a new model has become commercially available, the Mobetron 2000.…”
Section: Introductionmentioning
confidence: 94%
“…The PTW30013 Farmer type chamber (PTW, Freiburg, Germany) was used for this purpose. It was reported that the cylindrical PTW Farmer chamber and the parallel plate PTW Roos chamber agreed within 1 % for the 4 and 6 MeV energies, and within 0.5 % for the 9 and 12 MeV energies [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, a new generation of mobile linear accelerators like NOVAC7 (NRT, Aprilia, Italy), (3) Liac (Sordina SpA, Italy), (4) and Mobetron (IntraOp Medical, Inc. Santa Clara, CA) (5) have been designed to deliver radiation therapy in the operating theater. A NOVAC7 system has been installed at our hospital to be used specifically for breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%